2020
DOI: 10.1038/s41598-020-69131-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of add-on transcranial direct current stimulation on pain in Korean patients with fibromyalgia

Abstract: Despite promising preliminary results of transcranial direct current stimulation (tDCS) treatment in patients with fibromyalgia (FM), several issues need to be addressed, including its limited efficacy, low response rate, and poor tolerability. We investigated the efficacy and safety of tDCS as an add-on treatment for chronic pain in Korean patients with FM. This study enrolled 46 patients who were refractory to pain medications from May 2016 to February 2017. A conventional tDCS device was used to supply 2 mA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…The results indicated the effectiveness of pharmacotherapy in the components of miscellaneous pains, pain assessment, affective perception, and sensory perception. The results are consistent with the results of studies performed by Kim et al ( 9), Kang et al (24), and Ngernyam et al (25). Kang et al (24) suggest that tDCS can result in significant pain relief in patients with fibromyalgia and might be an effective add-on treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results indicated the effectiveness of pharmacotherapy in the components of miscellaneous pains, pain assessment, affective perception, and sensory perception. The results are consistent with the results of studies performed by Kim et al ( 9), Kang et al (24), and Ngernyam et al (25). Kang et al (24) suggest that tDCS can result in significant pain relief in patients with fibromyalgia and might be an effective add-on treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The results are consistent with the results of studies performed by Kim et al ( 9), Kang et al (24), and Ngernyam et al (25). Kang et al (24) suggest that tDCS can result in significant pain relief in patients with fibromyalgia and might be an effective add-on treatment. Ngernyam et al (25) observed a significant association between a decrease in pain intensity and an increase in peak theta-alpha frequency at the stimulation site in patients with neuropathic pain from spinal cord injury.…”
Section: Discussionsupporting
confidence: 91%
“…Briefly, a painless electric current is applied to the scalp and is believed to generate analgesic effects by modulating resting membrane potentials of neurons and pain processing pathways in the targeted cortical area [ 21 ]. Recent studies have shown preliminary efficacy in the clinical and home-based settings in patients with fibromyalgia and multiple sclerosis [ 18 , 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, as stated earlier, peripheral parameters affect the regulation of neuroinflammation. SG has been reported to affect peripheral parameters, such as coagulation reduction ( Kang J. H. et al, 2020 ; Kang W. S. et al, 2020 ), return of neuromuscular signals ( Biricik et al, 2019 ), and peripheral inflammation ( Yeşiltaş et al, 2021 ). Moreover, plasma inflammatory and neuronal injury markers have been reported by surgery and anesthesia procedures ( Subramaniyan and Terrando, 2019 ).…”
Section: Discussionmentioning
confidence: 99%